Pharmacokinetics of a New Tetramethylpyrazine Analogue CXC195 in Rats - Wei, C.; Kong, L.; Wei, X.; Chen, L.; Liu, X.; Zhang, X.; Liu, X.; Liu, H. (Drug Research, 2013)
To investigate the pharmacokinetical characteristics of a new neuroprotective drug CXC195 after intraperitoneal injection in rats.A single 10 mg · kg−1 of CXC195 was intraperitoneally injected to 8 rats after fasting overnight, respectively. 500 microliters of blood samples were collected at scheduled time before and after administration. CXC195 in rats’ plasma was separated on a Diamonsil C18 column (150 mm×4.6 mm, 5 μm), eluted using methanol − 0.05 mM NaH2PO4 solution (86:14, v/v) as mobile phase, and detected by UV detector at wavelength of 278 nm. The plasma concentration of CXC195 was determined by established HPLC method after disposition and its pharmacokinetic parameters were analyzed and evaluated by Drug and Statistic (version 2.0).The Cmax, Tmax, t1/2, AUC0-8, AUC0-∞, MRT0-8, MRT0-∞, CL/F and V/F of CXC195 aftersingle dose intraperitoneal injection of 10 mg · kg−1 CXC195 were 12.37±5.35 μg · mL−1, 0.5±0.21 h,4.24±2.43 h, 24.89±8.32 μg · mL−1 · h, 28.57±9.66 μg · mL−1 · h, 2.00±0.53 h, 2.93±0.75 h, 1.4±0.73 L · h−1 and 1.16±0.68 L.The established HPLC method was sensitive, rapid, and suitable for CXC195 pharmacokinetic study. The procedure of CXC195 in rat was fit to double-compartmental model with lag time of 0.13 h.
Keywords: CXC195; tetramethylpyrazine; pharmacokinetics; HPLC